Emotional Intelligence: Does It Matter in Education - Dick, Rhonda (Social Science Learning Education Journal, 2016)
For decades, traditional intelligence and personality have correlated with student performance in the classroom. Another theory, emotional intelligence (EI), has been emerging as an important area of research in education and in recent years has become a vital concept when considering educational policy. This article will provide a review of the most common EI models, the instruments or inventories utilized to measure each model, criticisms of EI theory, and a discussion on benefits and the implementation of EI in the classroom.